2018
DOI: 10.1373/jalm.2017.024307
|View full text |Cite
|
Sign up to set email alerts
|

Severe Isotype-Matched Immunosuppression (IMI) as a Potential Risk Factor for Progression of MGUS Patients

Abstract: Background: Monoclonal gammopathy of undetermined significance (MGUS) precedes multiple myeloma in virtually every case. However, only a small percentage will progress and at very different rates. In addition, recent data have suggested that MGUS is associated with other comorbidities including infections, suggesting impaired immune function in some MGUS patients. Therefore, we aimed at assessing the value of isotype-matched immunosuppression (IMI; e.g., suppression of an IgAκ in an IgAλ patient), a type of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…This finding did not reach statistical significance in IgA and IgM MGUS, probably due to the very low number of patients conforming some of the subsets. More importantly, as a result of a multivariate analysis, severe IMI, contrary to severe classical immunoparesis, was found to be an independent risk factor of progression from MGUS to symptomatic disease [53]. Similar results were obtained by Katzman and colleagues with IMI.…”
Section: At Diagnosissupporting
confidence: 84%
See 1 more Smart Citation
“…This finding did not reach statistical significance in IgA and IgM MGUS, probably due to the very low number of patients conforming some of the subsets. More importantly, as a result of a multivariate analysis, severe IMI, contrary to severe classical immunoparesis, was found to be an independent risk factor of progression from MGUS to symptomatic disease [53]. Similar results were obtained by Katzman and colleagues with IMI.…”
Section: At Diagnosissupporting
confidence: 84%
“…In asymptomatic patients, IMI seems to have an interesting role in identifying those patients with higher risk of progression. In MGUS, two large studies have found IMI to be an independent risk factor of progression [32,53]. In fact, the addition of the IMI to the stratification model developed by the Mayo Clinic resulted in the better identification of those patients at highest risk of progression.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the free light-chain test and other serum markers, the Hevylite test guarantees the excellent monitoring of patients with plasma cell dyscrasias [ 54 ]. Interestingly, a multivariate analysis conducted by Jimenez and colleagues demonstrates that severe IMI, rather than classical immunoparesis, is an independent risk factor of progression from MGUS to MM [ 54 , 55 ]. Thus, the IMI is an additional risk factor that is able to discriminate between high-risk MGUS patients [ 52 , 55 ].…”
Section: Hevylite Pair Suppressionmentioning
confidence: 99%
“…Interestingly, a multivariate analysis conducted by Jimenez and colleagues demonstrates that severe IMI, rather than classical immunoparesis, is an independent risk factor of progression from MGUS to MM [ 54 , 55 ]. Thus, the IMI is an additional risk factor that is able to discriminate between high-risk MGUS patients [ 52 , 55 ].…”
Section: Hevylite Pair Suppressionmentioning
confidence: 99%